استخدام ألعاب كلمة غامضة لترقية مهارة الكلام - Huda, Hisbullah; Ahmala, Majidatun; Putri, Indah Desiana; Rosidi, Muhammad Farhan (Prosiding Konferensi Nasional Bahasa Arab dan Pembelajarannya di Era Milenial, 2022)
This study discusses how to use the mysterious word game in learning Arabic, especially Maharah al-Kalam. Researchers used an Arabic game called mysterious word. Problems faced by researchers include students who think learning Arabic is difficult, and low interest in learning Arabic. Therefore, the researcher presents a mysterious word game to turn on an active and fun learning process. This study aims to find out whether this mysterious word game can increase maharah al-kalam. This research includes field research using qualitative methods. The mysterious word language game in Arabic learning can increase maharah al-kalam, because students interact and communicate a lot using Arabic in the game. This game is effective for speaking skills to communicate goals, namely using it in the process of teaching speaking skills, and to complete the standard test in accordance with the material to be taught by the teacher in class.